ANALISIS KERAGAAN AGROINDUSTRI KLANTING DI DESA GANTIMULYO KECAMATAN PEKALONGAN KABUPATEN LAMPUNG TIMUR - Aidawati, Gusti Ayu Komang Theresia; Murniati, Ktut; Riantini, Maya (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to analyze the procurement process of raw materials that correspond to six rights (time, place, quality, quantity, type, and price), klanting agroindustry profit, and marketing mix with 7P (product, price, promotion, place, people (human resources), process, and physical evidence). This research uses the case study method at Klanting Agrondustry in Gantimulyo Village Pekalongan District. The location was chosen purposively considering that the village is a klanting production center in East Lampung Regency. Data of this research were collected from December 2019 to January 2020. The method data analysis used in this research is a descriptive qualitative analysis and quantitative. The results of this research indicated that the procurement of raw materials has not fulfilled all the six components precisely, because it does not match reality expected by agroindustry owners on components on time, the right type, right quality, and right quantity. On the right place and right price component, it is accordance with the agroindustry owner’s expectations, because the location of raw materials is close to the agroindustry, and the price is low. The advantages of agroindustry are good, because it shows a positive advantage. That advantage obtained in one month at Mekar Sari Agroindustry amounting to IDR4,933,709.57, Mitra Tani Agroindustry amounting to IDR3,854,706.64, and Mitra Lestari Agroindustry IDR2,907,475.87. The agroindustry marketing strategy has implemented components of the 7P marketing mix, only the promotional components are missing applied optimally. Key words: agroindustry, klanting, marketing mix, performance